Preservation of local village rooster semen using Ringer's Diluent with 3 levels of Glycerol and Ethylene Glycol at chilled temperature (5 °C) - Muhammad Fahmi Ahmad (Universiti Malaysia Sabah, 2017)
The aim of this study is to evaluate the effect of 3 levels of glycerol and Ethylene glycol on the preservation of rooster sperm's quality and quantity. Ten roosters were selected and sperm from rooster village chicken were selected and sperm ejaculation was collected by abdominal massage method. Sperm ejaculation of three cockerels were pooled and extended using Ringer's Solution and they were categorized into 0%G, 2%G, 4%G, 6%G, O%EG, 2%EG, 4%EG, 6%EG as treatment groups. Extended semen from three different levels of glycerol were put In chilled (5°C) temperature. Semen evaluation was evaluated hourly over 72 hours. The best post-thaw motility scale for rooster village chicken after 72 hours are 4%EG (16.67%) followed by 2%G {13.33%). The highest percentages of live sperm were obtained with 6%G (27.55%) followed by 2%EG (19.56%) while the best post-thaw abnormal sperm was obtained with 6%G (68.89%) followed by 2%EG (68%). From this, we can conclude that glycerol with 6% level is better than 2% level of ethylene glycol for maintaining sperm viability and abnormality with significant level p<0.05.